Indonesia Islamic senior high school students’ English learning conceptions and strategies - Mulyani, Euis Rina; Suherdi, Didi; Sundayana, Wachyu (Indonesian Journal of Applied Linguistics, 2020)
This study was inspired by previous studies of how students’ learning influences their learning beliefs and, in turn, their strategies. Unfortunately, few studies concern learners’ conceptions of learning, in particular in learning English, and paid less attention to the senior high school students level. With the intention to identify Islamic senior high school. Interviews and both close and open questionnaires were used to collect relevant data. To identify students’ conception, Purdie and Hattie’s COLI items were used; and Oxford’s SILL to identify learning strategies. Data collected from the close questionnaire were analyzed by quantifying the frequency and the average of particular issues, which include the preference of students' learning conception and learning strategies. Meanwhile, data from interviews and open questionnaire were analyzed using Miles and Hubberman’s (1994) framework of qualitative data analyses. Overall, data analyses results showed that, in terms of their conceptions, most students conceived learning as a duty—in order to able to make their parents happy, to serve the community with their knowledge, and most of all, as a way to show their devotion to Allah the all mighty. In addition, most students favored metacognitive learning strategies in learning English. This study came to the conclusion that although the tendency of students’ conception of learning English was at the surface level of learning, most of the students used relatively complex and high-level strategies when it came to their English learning process as they used metacognitive strategies.